Pemilihan Bronkodilator Pada Penyakit Paru Obstruktif Kroni - Zen Ahmad (Conferences of Medical Sciences Dies Natalis, 2019)
Chronic obstructive pulmonary disease (COPD) is a disease that is often found, can be prevented and treated. It characterized by symptoms of persistent respiration and obstruction of airflow, associated with airway disorders and/or alveoli due to exposure to significant harmful particles or gases. COPD currently causes the world's fourth death and is projected to be third in 2020. In 2012, COPD has caused 3 million deaths (6% of all deaths) and will contribute 4.5 million deaths by 2030. COPD requires high costs especially in exacerbation conditions that require hospital treatment.Exposure to cigarette smoke or harmful agents will cause stimulation of macrophages and airway epithelium. Stimulation of macrophages will stimulate inflammatory processes and the underlying cascade such as protease formation and increased oxidative stress. One treatment of COPD is through pharmacological therapy approaches using a bronchodilator which aims to overcome airflow limitation with or without the addition of corticosteroids, mucolytics, antioxidants, and other drugs. The choice of bronchodilators in COPD patients is very individual. The selection must pay attention to the degree of the complaint, the magnitude of the risk of exacerbation, side effects, drug availability, costs, the presence of comorbid diseases and device inhalers.